Comparison of three different strategies to treat sciatic nerve regeneration: an experimental study - Smaniotto,Pedro Henrique (2022)
ABSTRACT Purpose: To compare the effect of vein conduit filled with adipose tissue stem cells (ASC) on peripheral nerve injury regeneration. Methods: We analyzed 30 male Wistar rats surgically submitted to a 5-mm gap on the sciatic nerve. Then, the animals were divided into three groups: nerve autografting (AG, n=10), autogenous inverted glycerol-conserved vein (VG, n=10), and autogenous inverted glycerol-conserved vein + ASC (VASCG, n=10). The study endpoints were neuromotor functional analysis, gastrocnemius muscle weight, and sciatic nerve graft histomorphometry analysis. In the histologic analysis, we added a control group (naïve nerve). Results: Regarding functional analysis (Walking tract- score), the findings at week 3 showed a difference between the AG and the VG (-96.6 vs. -59.6, p=0.01, respectively) and between the VG and the inverted vein + VASCG (-59.9 vs. -88.92, p=0.02). At week 12, this study showed a difference between the AG and the VG (-64.8 vs. -47.3, p=0.004, respectively), and also a difference between the VG and the VASCG (-47.3 vs. -57.4, p=0.02, respectively). There was no difference in the histomorphometry analysis (nerve diameter, Schwann cells counting). The gastrocnemius muscles on the intervention side were more atrophic when compared to the gastrocnemius muscles on the control side. Conclusions: Our results suggested better functional recovery in the inverted vein group when compared to control group, and inverted vein + ASC group.